2005
DOI: 10.1016/j.yexcr.2005.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Chinese hamster ORC subunits dynamically associate with chromatin throughout the cell-cycle

Abstract: In yeast, the Origin Recognition Complex (ORC) is bound to replication origins throughout the cellcycle, but in animal cells, there are conflicting data as to whether and when ORC is removed from chromatin. We find ORC1, 2 and ORC4 to be metabolically stable proteins that co-fractionate with chromatin throughout the cell-cycle in Chinese hamster fibroblasts. Since cellular extraction methods cannot directly examine the chromatin binding properties of proteins in vivo, we examined ORC:chromatin interactions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 83 publications
(131 reference statements)
7
39
0
Order By: Relevance
“…A similar dynamic behavior was also reported for ORC components (45). In contrast, a recent study showed stable binding of MCM proteins to chromatin in CHO cells (48).…”
Section: A System For Studying MCM Protein Dynamics Within Livesupporting
confidence: 83%
See 1 more Smart Citation
“…A similar dynamic behavior was also reported for ORC components (45). In contrast, a recent study showed stable binding of MCM proteins to chromatin in CHO cells (48).…”
Section: A System For Studying MCM Protein Dynamics Within Livesupporting
confidence: 83%
“…We have estimated an apparent residence time of 1-2 h on the basis of FLIP analysis, whereas earlier work indicated even longer residence times for MCM proteins in Chinese hamster ovary cells (48). In contrast, other components of the prereplication complex, such as ORC (45) and Cdt1 (46,47), dissociate completely from chromatin within seconds or minutes. This is consistent with in vitro work in Xenopus egg (63) and yeast extracts (64,65) that showed that the MCM hexamer can be stably loaded on chromatin, whereas ORC and Cdt1 can be subsequently washed away.…”
Section: Discussionmentioning
confidence: 88%
“…The degradation of ORC1 may not be a consistent regulatory feature, as it is observed in some cells but not in others. [18][19][20] The importance of Cdc6 nuclear export is controversial due to conflicting reports on the extent of nuclear export, as described below. Overexpression of a non-degradable Cdt1 produces limited DNA re-replication (significantly less than in fission yeast).…”
Section: The Prevention Of Dna Re-replication In Yeast and Metazoansmentioning
confidence: 99%
“…These and other studies suggest that, while the protein levels and chromatin association of Orc2-6 remain constant throughout the cell cycle, Orc1 is selectively removed following origin activation until the next cell cycle. However, it is not clear how the biochemical or cytological behavior of the bulk population of ORC contributes to DNA replication regulation (34).…”
mentioning
confidence: 99%